Intermediate cities in search of sustainability : the research and the Attica workshop: Lavrion, 4-6 October 1995. - Mega, Voula (Office for Official Publications of the European Communities, 1996)
The Attica Workshop (Lavrion, 4-6- October 1995) has been an important step in the framework of our research on medium-sized cities and socio-economic and environmental developments in the regions of the EU. It marked the completion of most of the 15 case studies on 15 selected cities and the starting point for the synthesis of their developmental problems and perspectives. This publication includes both significant pieces of the ongoing research and papers from the Attica Workshop and has the ambition to offer experts and decision makers something of the very essence of the ongoing research and of a colloquium in Attica, at the beginning of autumm 1995.